Programming DNA Nanoassembly for Enhanced Photodynamic Therapy. (9th December 2019) - Pan, Min; Jiang, Qunying; Sun, Junlin; Xu, Zhen; Zhou, Yizhuo; Zhang, Li; Liu, Xiaoqing
Abstract: Photodynamic therapy (PDT) has extraordinary promise for the treatment of many cancers. However, its clinical progress is impaired by the intrinsic hypoxic tumor microenvironment that limits PDT efficacy and the safety concern associated with biological specificity of photosensitizers or vehicles. Now it is demonstrated that rationally designed DNA nanosponges can load and delivery photosensitizer effectively, target tumor precisely, and relieve hypoxia‐associated resistance remarkably to enhance the efficacy of PDT. Specifically, the approach exhibits a facile assembly process, provides programmable and versatile nanocarriers, and enables robust in vitro and in vivo anti‐cancer efficacy with excellent biosafety. These findings represent a practical and safe approach by designer DNA nanoassemblies to combat cancer effectively and suggest a powerful strategy for broad biomedical application of PDT. Abstract : Schwamm drüber ! Designer‐DNA‐Nanoschwämme entlasten Hypoxie‐zugehörigen Widerstand und verbessern die photodynamische Therapie (PDT). Der einfache Assemblierungsprozess, die robuste therapeutische In‐vitro‐ und In‐vivo‐Wirksamkeit sowie die gute Biosicherheit demonstrieren eine praktische PDT‐Plattform für biomedizinische Anwendungen. Zudem weist der Ansatz darauf hin, dass DNA‐Nanotechnologie großes Potential für erweiterte Therapeutika aufweist.